The End of Television—Again! How TV Is Still Influenced by Cultural Factors in the Age of Digital Intermediaries - Enli, Gunn (2016)
This article discusses the impact of convergence and digital intermediaries for television as a medium, industry and political and cultural institution. There is currently widespread debate about the future of television and the impact of technological and market changes. Our argument is that the answer to what is happening to television cannot be adequately addressed on a general level; local and contextual factors are still important, and so is the position and strategic response of existing television institutions in each national context. Based on analyses of political documents, statistics, audience research and media coverage, as well as secondary literature, the article explores the current situation for Norwegian television and point to four contexts that each plays a part in constraining and enabling existing television operators: the European context, the public service context, the welfare state context and the media ecosystem context.